Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Parallel title: Sustaining Impact in CLC Schools and Communities
Keywords: Official Language Minority Community (OLMC)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Artful Inquiry : Transforming Understanding Through Creative Engagement - Leading English Education and Resource Network (LEARN) (2016)
Number of pages: 552

Sustaining Impact in CLC Schools and Communities : Provincial Resource Team Report : 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)